Resource Management and Area Promotion by the Collaboration of Rural and Urban People in Rural Area -The case study on development from environmental conservation to tourism and area promotion on Shimanto-river basin in Kochi prefecture- - Katsuhisa Ito (European Regional Science Association (ERSA), 2010)
In this paper, I discussed on the change of environment conservation, resource management, area promotion and their policies, and significance and problems in the case of Shimanto-river basin in Shikoku district. Shimanto-river became famous as 'the last clear river in Japan' by television program, which have resulted the increase of tourists, and tourism of river leisure activity and rural experience activity became popular. The movement in Shimanto-river basin had begun from environment conservation, and gradually had added new movement like tourism and area promotion. Also, many players like local government, local enterprise, NPO, inhabitants, volunteers, tourists, and city residents, have participated in the movement. On the consensus among stakeholders of the movement was easy on environment conservation and tourism due to ethic and pragmatic reasons, but on collaboration management of land resource like paddy field and forest were difficult to make consensus, due to land ownership. There are much of abandoned paddy field and forest land recently. It must be permitted by landowner naturally to maintain the lands by volunteers or city residents of well-meaning, even if abandoned lands. Therefore new policy which separates ownership and management system will be needed.
Keywords: 330; Collaboration of rural and urban people; Resource management; Area promotion; Consensus; Legitimacy